Localização visual de objetos utilizando uma cabeça robótica com visão estéreo - Dias, Eduardo Tondin Ferreira (2009)
This paper describes the development of a platform for simulation of movements of the human visual system, using techniques for object detection and control algorithms. The image processing and robotic head control methods are described, as well as the results obtained and ideas for future research.